A GAL4‐inducible transgenic tool kit for the in vivo modulation of Rho GTPase activity in zebrafish. Issue 8 (17th May 2016) - Hanovice, Nicholas J.; McMains, Emily; Gross, Jeffrey M.
Abstract : Background: Rho GTPases are small monomeric G‐proteins that play key roles in many cellular processes. Due to Rho GTPases' widespread expression and broad functions, analyses of their function during late development require tissue‐specific modulation of activity. The GAL4/UAS system provides an excellent tool for investigating the function of Rho GTPases in vivo. With this in mind, we created a transgenic tool kit enabling spatial and temporal modulation of Rho GTPase activity in zebrafish.Results: Transgenic constructs were assembled driving dominant‐negative, constitutively active, and wild‐type versions of Cdc42, RhoA, and Rac1 under 10XUAS control. The self‐cleaving viral peptide F2A was utilized to allow bicistronic expression of a fluorescent reporter and Rho GTPase. Global heat shock of hsp70l: gal4 + transgenic embryos confirmed GAL4‐specific construct expression. Western blot analysis indicated myc‐tagged Rho GTPases were expressed only in the presence of GAL4. Construct expression was confined to proper cells when combined with pou4f3 :gal4 or ptf1a :gal4. Finally, transgene expression resulted in reproducible defects in lens formation, indicating that the transgenes are functional in vivo.Conclusions: We generated and validated 10 transgenic lines, creating a versatile tool kit for the temporal‐spatial modulation of Cdc42, RhoA, and Rac1 activity in vivo. These lines will enable systematic analysis of Rho GTPase function in any tissue of interest. Developmental Dynamics 245:844–853, 2016 . © 2016 Wiley Periodicals, Inc. Key findings: Transgenics enabling GAL4‐mediated induction of DN, CA and WT Cdc42, RhoA and Rac1 expression. F2A fusions were made between Rho GTPases and a fluorescent marker to enable in vivo tracking of expressing cells.